Validation of the psychometric properties of a "Modified Version of the Hornheider Screening Instrument" (HSI‐MV) using a sample of outpatient and inpatient skin tumor patients. (15th April 2022) - Buchhold, Britta; Lutze, Stine; Freyer‐Adam, Jennis; Jünger, Michael; Ramp, Marleen; Konschake, Wolfgang; Jülich, Andreas; Nordt, Claudia; Peters, Sebastian; Arnold, Andreas; Hannich, Hans‐Joachim
Summary: Background: The basis for adequate psycho‐oncological care is the identification of patients with psychosocial support needs. The German Working Group for Psychooncology also recommends the Hornheider Screening Instrument (HSI) for this purpose. The question, "Is anyone in your family particularly burdened by the hospital stay?" is intended to capture disease‐related family stress. But is this item equally suitable for outpatients and inpatients? The study objective was to examine how replacing the original item affects the test performance of this modified version of the HSI and the frequency of psychosocial stress. Patients and Methods: 92 outpatients and 98 inpatients with skin tumors assessed their psychosocial situation using different questionnaires. Results: Compared to inpatients, less than half as many outpatients answered the item in the affirmative. If the question was replaced by: "Is someone in your family particularly burdened by your disease or the course of the disease?" this setting‐related difference did not arise. The "Alternative item" and the "Modified version of the HIS" (HSI‐MV) proved to be superior to the original item and the original HSI with regard to all examined criteria. Conclusions: The HSI‐MV can be used as a reliable and valid instrument for the systematic assessment of psychosocial care needs in outpatient and inpatient settings. Depending on care capacity, a threshold of ≥ 5 or ≥ 4 is appropriate. In addition to screening, the desire for support should be enquired.